Effect of the Stress State Triaxiality on the Value of Limit Strain of Micro-Void Development in S235JR Steel – Numerical Analysis - Wcislik, Wiktor (Communications - Scientific letters of the University of Zilina, 2011)
This paper deals with the numerical analysis of plastic deformation and damage development in S235JR steel in complex stress states. The material Gurson Tvergaard Needleman (GTN) model was applied. The analysis was performed for notched bars subjected to tension. An attempt was made to investigate the effect of stress triaxiality on the value of critical strain of voids growth in the GTN model.